Biosynthesis of Silver Nanoparticles from Embryogenic Calli of Alhagi maurorum - Sehrawat, Anita Rani (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: Synthesis of silver nanoparticles (SNPs) from plant-derived callus seems to be a convenient and easy approach in comparison to traditionally used physical and chemical methods. Introduction: Highly active, young mass of cells of callus not only produce chemicals (reducing/oxidizing agent) used for the reduction of silver ions to SNP but also prevent the formation of aggregates, and thus, highly dispersed nanosilver were obtained from embryogenic calli. Methods: In the present studies, Alhagi maurorum explant (nodal portion of stem) was cultured on the MS medium supplemented with different combinations of BAP, NAA, and kinetin along with other adjuvants for callusing, shoot formation, multiplication, and rooting of elongated plantlets. Highly differentiated calli, thus, obtained were used for the synthesis of SNP. Results and Discussion: The change of the color of the reaction mixture after 15 min from yellow to dark reddish brown indicated the synthesis of nanoparticles from callus. Ultraviolet–visible spectra at 450 nm showed the characteristic of SNP in the callus. Transmission electron microscopic observations and Fourier transform infrared spectroscopy studies confirmed the formation of nano-sized silver crystallites (10–30 nm), and role of different functional groups (carboxyl, amine, and hydroxyl) in the synthetic process, respectively. Conclusions: Thus, callus derived SNP was biocompatible, non-toxic, eco-friendly, and cost-effective and could be used as decontaminating agent in plant tissue culture.